Diabetic complications do not hamper improvement of health-related quality of life over the course of treatment of diabetic foot ulcers - the Eurodiale study - Siersma, Volkert; Thorsen, Hanne; Holstein, Per E; Kars, Marleen; Apelqvist, Jan; Jude, Edward B; Piaggesi, Alberto; Bakker, Karel; Edmonds, Michael; Jirkovská, Alexandra; Mauricio, Didac; Reike, Heinrich; et al. (Journal of diabetes and its complications, 2017)
AIMS: Diabetic complications, and in particular diabetic foot ulcers (DFUs), are associated with low health-related quality of life (HRQoL). We evaluated whether the presence of diabetic complications also influenced the improvement of HRQoL during DFU treatment. METHODS: 1088 patients presenting for DFU treatment at the centers participating in the Eurodiale study were followed prospectively up to one year. HRQoL was measured both at presentation and after healing or at end of follow up, using EQ-5D: a standardized instrument consisting of five domains and a summary index. The influence of diabetic comorbidity on the course of HRQoL was evaluated for each of the EQ-5D outcomes in multi-level linear regression analyses, adjusting for baseline characteristics. RESULTS: HRQoL improved in all EQ-5D outcomes over the course of treatment for those DFUs that healed. The few significant differences in the development of HRQoL between patients with and without comorbidity showed a more beneficial development for patients with comorbidity in DFUs that did not heal or healed slowly. CONCLUSIONS: Comorbidity does not hamper improvement of HRQoL in DFU treatment. On the contrary, HRQoL improved sometimes more in patients with certain comorbidity with hard-to-heal ulcers.
Keywords: kombinovaná terapie; Longitudinal study; diabetická noha; Comorbidity; kvalita života; kohortové studie; Combined Modality Therapy; Diabetes Complications; Male; longitudinální studie; Middle Aged; Quality of Life; Self-Management; Health-related quality of life; Cohort Studies; Diabetes mellitus; Europe; Aged; Prospective Studies; činnosti denního života; mužské pohlaví; senioři; deprese; Cost of Illness; komplikace diabetu; Diabetic Foot; Diabetic foot ulcer; komorbidita; Evropa; self-management; úzkost; lidé; Wound Healing; ženské pohlaví; Humans; Activities of Daily Living; Longitudinal Studies; psychiatrické posuzovací škály; Female; Depression; Psychiatric Status Rating Scales; lidé středního věku; Anxiety; osobní újma zaviněná nemocí; hojení ran; prospektivní studie